REVIEW: MANFAAT ASAM KLOROGENAT DARI BIJI KOPI (Coffea) SEBAGAI BAHAN BAKU KOSMETIK - Retty Handayani; Fadzilla Muchlis (Universitas Pakuan, 2021)
Chlorogenic acid(Chlorogenicacid,CGA) is one of the secondary metabolites produced from coffee beans. Chlorogenic acid is widely used in cosmetic preparations as an exfoliant (exfoliate). Apart from exfoliating, chlorogenic acid can also be used as an antioxidant, natural cosmetic coloring, antibacterial (acne), cellulite and slimming. In review this, first look at the comparison of the concentration of chlorogenic acid in the two types of coffee, namely Arabica coffee and Robusta coffee. Next, determine several cosmetic preparations that use coffee beans as a natural ingredient which contains chlorogenic acid. The purpose of review thisis to determine the comparison of the concentration of chlorogenic acid from Arabica coffee beans and robusta coffee which can be used in various cosmetic preparations. Based on the data obtained, the highest chlorogenic acid content was found in robusta green coffee beans with a concentration of 6.1-11.3 (g / 100g), while in Arabica green coffee beans with a concentration of 4.1-7.9 (g / 100g). So it can be concluded that the chlorogenic acid content in robusta coffee has a higher content compared to arabica coffee so that robusta coffee is more recommended to be used as a cosmetic raw material.